The Rediscovery of Moral Beauty, Truth, and Hope: Awakening the Moral and the Religious Sense - Ramos, Alice (Studia Bioethica, 2013)
Much of contemporary culture seems to be fixated on a superficial beauty, only on what the eyes can see; the emphasis is on sensible beauty, on cosmetic beauty. There is what may be called a cult of beauty, as is evidenced by the “extreme makeover” television shows in the United States and by the recourse to cosmetic surgery both among the young and the not so young. And yet this cult does not make people happy, for as we know beauty is fleeting; it is ephemeral. Perhaps our taste for this type of beauty is an indication of the nihilistic philosophy which pervades so much of our culture today.